Recent advances in therapies utilizing superabsorbent hydrogel technology for weight management: A review - Louis J. Aronne; John E. Anderson; Alessandro Sannino; Elaine Chiquette (Wiley, 2022)
Abstract Long‐term therapeutic benefit of treatments for weight management in patients with overweight (also termed preobesity) or obesity may be limited by variable safety, tolerability, and efficacy profiles, and patient adherence to treatment regimens. There is a medical need for nonsystemic treatments that promote weight loss in patients with overweight or early obesity. This report reviews four different approaches of utilizing superabsorbent hydrogel technology for weight management at varying stages of preclinical and clinical development. The first is a nonsystemic, oral superabsorbent hydrogel created from naturally derived building blocks used in foods (cellulose‐based), designed to mix homogenously with and change the properties of the ingested meal throughout the gastrointestinal tract (stomach and small intestine). This is the first‐in‐class to be cleared by the Food and Drug Administration (FDA) to aid in weight‐management for adults with BMI of 25-40 kg/m2 in conjunction with diet and exercise. In contrast, the other three approaches in development utilize superabsorbent hydrogel technologies to support an intragastric balloon‐like structure, solely occupying space in the stomach and displacing the meal: (1) a pufferfish‐inspired device; (2) Epitomee, a pH‐sensitive self‐expanding hydrogel device; and (3) a light‐degradable hydrogel used to control balloon deflation. These new approaches that utilize superabsorbent hydrogel technology offer a wide range of clinical applicability and have the potential to broaden the weight management treatment landscape. Over time, increasing the number of patients treated with superabsorbent hydrogel technologies will provide important information on long‐term efficacy and safety.